2021
DOI: 10.3390/diagnostics11040635
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Speckle Tracking Echocardiography in the Evaluation of Common Inherited Cardiomyopathies in Children and Adolescents: A Systematic Review

Abstract: Speckle tracking echocardiography (STE) has gained importance in the evaluation of adult inherited cardiomyopathies, but its utility in children is not well characterized. We conducted a systematic review to evaluate the role of STE in pediatric inherited cardiomyopathies. PubMed, EMBASE, Web of Science, Scopus, CENTRAL and CINAHL databases were searched up to May 2020, for terms related to inherited cardiomyopathies and STE. Included were dilated cardiomyopathy (DCM), hypertrophic cardiomyopathy (HCM), left v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 43 publications
1
7
0
4
Order By: Relevance
“…According to this study, LV torsion was higher in the HCM group than that in the HHD group and, therefore, the assessment of LV torsion was shown to provide discriminative ability between patients with HCM and HHD. Increased LVEF was also found in patients with HCM, which was consistent with a previous study ( 27 ). The deformation parameters (GLS, GRS, GCS, and torsion) showed underlying effects on contractile function for both the cardiac hypertrophied entities.…”
Section: Discussionsupporting
confidence: 93%
“…According to this study, LV torsion was higher in the HCM group than that in the HHD group and, therefore, the assessment of LV torsion was shown to provide discriminative ability between patients with HCM and HHD. Increased LVEF was also found in patients with HCM, which was consistent with a previous study ( 27 ). The deformation parameters (GLS, GRS, GCS, and torsion) showed underlying effects on contractile function for both the cardiac hypertrophied entities.…”
Section: Discussionsupporting
confidence: 93%
“…There are some differences when looking at deformation parameters, with reduced longitudinal strain and strain rates when assessed segmentally but with global values remaining within normal range in a larger proportion of pediatric cases. 68 With regard to torsion, some pediatric studies have shown altered basal rotation but with preserved and even increased apical rotation. 69…”
Section: Assessment Of Left Ventricular Systolic Functionmentioning
confidence: 99%
“…Для выявления диастолической функции ЛЖ на ранних стадиях заболевания целесообразно использовать тканевое допплеровское исследование скорости движения фиброзного кольца митрального и трикуспидального клапанов. Анализ систолической функции ЛЖ можно провести по показателям сократимости желудочков (dP/dt), деформа-ции ЛЖ [2,39]. В педиатрии необходимо определять отклонения от нормы c учетом весо-ростовых показателей ребенка в последовательных ультразвуковых исследованиях для подтверждения прогрессирования, стабильности или регресса заболевания [40,41].…”
Section: диагностикаunclassified
“…У данной категории детей выявляется снижение деформационных свойств ЛЖ, в первую очередь снижение деформации ЛЖ в продольном направлении. На группах детей с ДКМП проведено всего лишь несколько исследований, в которых прогностического значения величины глобальной деформации ЛЖ в продольном направлении пока не установлено [39].…”
Section: диагностикаunclassified
See 1 more Smart Citation